2018
DOI: 10.1111/pce.13403
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in cytokinin maintenance improves salt tolerance in apple rootstocks

Abstract: Plants experiencing salt-induced stress often reduce cytokinin levels during the early phases of stress-response. Interestingly, we found that the cytokinin content in the apple rootstock "robusta" was maintained at a high level under salt stress. Through screening genes involved in cytokinin biosynthesis and catabolism, we found that the high expression levels of IPT5b in robusta roots were involved in maintaining the high cytokinin content. We identified a 42 bp deletion in the promoter region of IPT5b, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 74 publications
(92 reference statements)
1
31
0
Order By: Relevance
“…Some studies have shown that under salt stress, the cytokinin content of apple rootstock 'robusta' remains high [97] and the cytokinin level in tomato seedlings also increases [4]. In addition, the cytokinin levels related to salt stress also increase in rice, Arabidopsis, and other plants [98,99].…”
Section: Salt Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that under salt stress, the cytokinin content of apple rootstock 'robusta' remains high [97] and the cytokinin level in tomato seedlings also increases [4]. In addition, the cytokinin levels related to salt stress also increase in rice, Arabidopsis, and other plants [98,99].…”
Section: Salt Stress Responsementioning
confidence: 99%
“…Exogenous methyl jasmonate (MeJA) pretreatment of wheat can maintain the high content of cytokinin by decreasing CKX transcription level induced by salt stress, reduce the delay of salt on seedling growth, and enhance salt tolerance [101]. Due to the deletion of 42 bp in the promoter region of the IPT5 gene, the expression level is increased along with the cytokinin content of apple rootstock 'robusta' under salt stress which was maintained at a high level and enhanced salt tolerance [97]. High cytokinin content in the tomato of SlIPT3 overexpression significantly improves salt tolerance by maintaining normal photosynthetic pigment and a high K + /Na + ratio [102].…”
Section: Salt Stress Responsementioning
confidence: 99%
“…Soil salinity is a major type of abiotic stress that limits crop productivity and affects plant growth and development. More than 800 million hectares of land is affected by salinity, and this problem continues to worsen (Liang et al, 2018;Yang and Guo, 2018;Feng et al, 2019). Apples (Malus domestica Borkh.)…”
Section: Introductionmentioning
confidence: 99%
“…The salt treatment consisted of the addition of 100 mM NaCl to ½ Hoagland's solution; the alkali treatment consisted of Na 2 CO 3 until pH = 9.0. The salt-alkali stress treatment consisted of the addition of both 100 mM NaCl and Na 2 CO 3 until pH = 9.0 to the nutrient solution [76,77].…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%